Investigating the use of visualization to improve public participation in infrastructure projects: how are digital approaches used and what value do they bring?. Issue 1 (1st January 2021) - Skaaland, Eivind; Pitera, Kelly
ABSTRACT: Using digital visualization models is suggested as a way of overcoming known barriers in public participation processes. Through a survey conducted among professional practitioners in the Norwegian infrastructure industry, different visualization models were compared in order to determine how they may lead to change in understanding and engagement among the public. The results indicated that digital visualization models were believed to lead to a statistically significant increase in people's understanding and engagement compared to traditional visualization models. In spite of this indication, it was traditional visualization models that were most commonly used to disseminate information about infrastructure projects to the public. The results also revealed that practitioners believed that 3D models in particular led to better understanding and increased engagement compared to virtual and augmented reality models; however, the latter models had seldom been used in infrastructure projects, and many of the respondents were not familiar with these visualizations. The results suggest that an increase in the use of digital visualizations could be beneficial. Additionally, more frequent, formal, and structured evaluation of the use of visualization should be done in order to ensure that the visualizations used meet specific project objectives.